Neurodevelopmental outcome of children with severe acute malnutrition - Irfan B. Bhat; Muzafar Jan; Abdus S. Bhat (International Journal of Contemporary Pediatrics, 2023)
Background: Severe acute malnutrition is known to be a major risk factor for impaired motor, cognitive, and socio-emotional development. Not much work has been done to study the neuro development of these patients. The aim of this study was to assess the neurodevelopment and outcome of children between 1 and 30 months with diagnosis of SAM Methods: The study was an observational prospective study conducted from November 2018 to April 2020. A total of 61 patients were enrolled in our study. Patients admitted in NRC with diagnosis of SAM were assessed for neurodevelopment after stabilization. Developmental assessment scale of Indian infants was used to calculate the motor developmental quotient and mental developmental quotient. Patients were followed till 6 months and after 6 months, they were again assessed by DASII to see the improvement in neurodevelopment status. Developmental quotient of less 70 was taken as delayed. Results: Mean DMeQ after stabilization and at 6 months after discharge was 53.672 and 72.591 respectively. Mean DMoQ after stabilization and at 6 months after discharge was 50.50 and 68.23 respectively. Mean DQ after stabilization and at 6 months after discharge was 52.186 and 70.4105 respectively. Conclusions: Severe acute malnutrition results in neurodevelopmental impairment in children but early and effective intervention results in significant improvement in neurodevelopment status.